A survey: Challenges of image segmentation based fuzzy c-means clustering algorithm - Alomoush W.; Alrosan A.; Norwawi N.; Alomari Y.; Albashish D.; Almomani A.; Alqahtani M. (Little Lion Scientific, 2024)
Indexed by SCOPUS/ERA